Remunerasi, Financial Efficacy dan Financial Well-Being - Aini, Nur; Hadiyati, Ernani; Muawanah, Umi (E-Jurnal Akuntansi; Vol 32 No 2 (2022)DO - 10.24843/EJA.2022.v32.i02.p09, 2022)
This study aims to examine and analyze the effect of remuneration and financial efficacy on financial well-being. The study used a quantitative approach and data was obtained by distributing questionnaires. Research respondents are administrative employees of state universities in Malang City. The questionnaires that were returned and declared eligible to be used as research data were 146 respondents, and then analyzed using SEM-PLS. The results showed that remuneration and financial efficacy had a positive effect on financial well-being. Financial efficacy has also succeeded in mediating the relationship between remuneration and financial well-being, although the value is relatively small. Remuneration as a form of compensation has been shown to increase financial well-being and financial efficacy contributes to strengthening this relationship. Keywords: Remuneration; Financial Efficacy; Financial Well-Being .